A review : dominance, marital satisfaction and female aggression - Edalati, Ali; Redzuan, Ma’rof (2010)
Several studies conducted on dominance, marital satisfaction and female aggression (physical and psychological) are the primary concern of the review done in this study. This article contains two parts; the first part touches on the findings which show female dominance has relationship with aggression. The second section is concerned on studies which have shown marital satisfaction has correlation with female aggression. According to the existing literature, the rate of female aggression has relationship with dominance and marital satisfaction. Nevertheless, in spite of this fact, less research has been carried out on dominance, marital satisfaction and female aggression to achieve better family life and a better society in general. Conclusion: Without the studies on women aggression, the conflict behavior in the family related to aggression will not be solved. Researchers must pay more attention towards female aggression.